A formação continuada de professores que ensinam matemática, centrada na resolução de problemas e em processos do pensamento matemático - Chaparin, Rogério Osvaldo (2019)
This work is related to teacher training, specifically in the continuing training of mathematic teaching teachers. We are part of the Algebric Education Research Group (GPEA). Our research inserts itself in the project The Mathematic in the Scholar Structure and Teachers Formation and Mathematic History, Epistemology and Didactics. It is based on a research that aimed to study possible changes in the actions of the teachers, during and after the experience of a continuing education course, focused on problem solving and mathematical thinking processes. A qualitative approach was used as research and teaching methodology based on the didactic engineering phases: The Theory of Didactic Situations of G. Brousseau, in connection with the ideas on Problem Solving, mainly from the point of view of G. Polya and F. Lester, were applied. The study considered the data resulting from 37 of 51 teachers from the state of São Paulo – Brazil that attended an 30 hour course in eight encounters that approached: open challenges and problems; problem resolution strategies; investigatives activities; problem resolution and mathematical thinking; algebrical and geometrical thoughts. Our goal was to propose tasks to develop the processes of mathematical thinkings. So activities were selected according with Blanco, that must allow: to abstract, to convince, to apply, to classify, to organize, to represent, to generalize, to compare, to explain, to conjecturize, to analize, to sinthesise, to explain and others. We highlighted that resolutions made by the teachers evolved from the first meeting to the last. In the end, there is the realization that the resolutions are centered in the process: elaboration of personal strategies, concern with justifications and argumentations. The ideas of Mason, Burton e Stacey that the problem resolution must be centered in the mathematical thought are considered according to the processes of: specialization, generalization, conjectures elaboration and justification. The following data were analyzed: each subject profile questionnaire, the writing production of the subjects in the personal encounters and in the application of problem resolution in a classroom. The analysis made evidenciated some changes in their perception about: productivity in problem resolutions when working in duos or trios; learning of the many types of problems; discussion about the diferente strategies during the institutionalizations. Therefore, we conclude that the course propiciated changes in the teachers practices in theirs classrooms, as they began to incorporate problems resolutions in their class activities